Pregnancy outcome among working women. - Ahlborg Jr., G.; Hogstedt, Christer; Bodin, Lennart; Barany, S. (Scandinavian Journal of Work, Environment & Health, 1989)
The influence of occupational factors on the outcome of pregnancy was investigated in a prospective study of 3901 women who worked during their pregnancy and received prenatal care in Orebro County from October 1980 to June 1983. Data on occupational factors, social circumstances, and life-style factors were obtained from questionnaires. There were no significant differences in the incidence of adverse pregnancy outcome (spontaneous abortion, perinatal death, birth defects, or low birthweight) between the nine occupational categories used when nonoccupational factors were accounted for. No increased risk was found for exposure to organic solvents, but the adjusted risk ratio of adverse outcome was 1.28 (95% CI 0.91-1.80) for "other chemical exposures." The work conditions in this county have been generally favorable in recent years, and the results therefore cannot be generalized to conditions with higher exposures. Methodological problems such as misclassification of exposure and the possible bias resulting from different rates of legal abortions among occupational groups are discussed.